EFEKTIFITAS PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Idris Harun (POTENSIA: Jurnal Kependidikan Islam, 2015)
This research aims to describe the use of information and communication technologies in the learning of Islamic Education. Information and communication technology is electronic equipment consisting of hardware and software as well as all activities related to the processing, manipulation, management, and transfer of information antarmedia. Information and communication technology serves to produce quality information and communicative communication. This technology includes communications systems such as computers, televisions, video, and internet. This technology serves as a medium, and learning resources. The use of this technology in the learning of Islamic education will be able to facilitate the achievement of learning objectives and provide the learning motivation to learners so that they will be used to learn independently in search of information about the learning materials through the medium of information and communication technology.